Þagnarmúr - Arnaldur Indriðason 1961- (Vaka-Helgafell, 2020)
Arnaldur Indriðason has long since proven himself as one of the masters of the Nordic Noir genre. Novels like Mýrin, Grafarþögn, Harðskafi and many others have made that abundantly clear. Secrets and walls of silence are the key themes here as retired policeman Konráð sets out to uncover past injustice and violence.